Odpowiedzi

  • Użytkownik Zadane
2010-02-25T17:35:58+01:00
A) -3x=2x-10
-5x=-10
x=2

b) 2x-2=7-x
3x=9
x=3

c) 10=4-2x
6=-2x
x=-3

d) -(2x-1)=4
-2x+1=4
-2x=3
x=-1½

e) 2(x+1)=x
2x+2=x
x=-2

f) 2t-(3t+1)=6
2t-3t-1=6
-t=7
t=-7

g) -(4+x)=2(3-x)
-4-x=6-2x
x=10

h) 3(y+6)-y=2(y+9)
3y+18-y=2y+18
2y+18=2y+18
0=0

i) (x-7)-2(3x+5)=3
x-7-6x-10=3
-5x-17=3
-5x=20
x=-4
2010-02-25T17:38:56+01:00
A) -3x=2x-10/-2x
-5x=-10/:5
-x=-2
b) 2x-2=7-x/-x
x-2=7/-2
x=5
c)10=4-2x/-4
6=2x/:2
x=3
d) -(2x-1)=4/+1
-2x=5
e) 2(x+1)=x
2x+1=x+1/-1
2x=1
f) 2t-(3t+1)=6/-1
2t-3t=5
-t=5


2010-02-25T17:39:03+01:00
A) -3x=2x-10
-3x-2x=-10
-5x=-10/:(-5)
x=2

b) 2x-2=7-x
2x+x=7+2
3x=9/:3
x=3

c) 10=4-2x
2x=4-10
2x=-6/:2
x=-3

d) -(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3/:(-2)
x=-3/2

e) 2(x+1)=x
2x+2=x
x=-2

f) 2t-(3t+1)=6
2t-3t-1=6
-t=7/*(-1)
t=-7

g) -(4+x)=2(3-x)
-4-x=6-2x
x=10

h) 3(y+6)-y=2(y+9)
3y+18-y=2y+18
0=0

i) (x-7)-2(3x+5)=3
x-7-6x-10=3
-5x=20/:(-5)
x=-4